2009
DOI: 10.1001/archgenpsychiatry.2009.10
|View full text |Cite
|
Sign up to set email alerts
|

Organization of Cognitive Control Within the Lateral Prefrontal Cortex in Schizophrenia

Abstract: In schizophrenic patients, the architecture of cognitive control follows the cascading organization from rostral LPFC regions to caudal LPFC and premotor regions depending on the temporal framing of action and events. We found, however, that immediate contextual signals insufficiently bias the caudal LPFC activity required to select the appropriate behavioral representation. This specific deficit could thus alter the internal consistency of schizophrenic patients' behavior. To compensate for this weakening of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 68 publications
1
33
0
Order By: Relevance
“…It is possible that both patients and siblings can indeed employ the reappraisal strategy in a laboratory setting, which is likely to be more structured and less complex than situations encountered in daily life. Barbalat et al [54] demonstrated that an increase of complex contextual information was related to reduced task performance in patients with schizophrenia. Interestingly, an increase of complex contextual information was associated with hypoactivation in the left VLPFC in patients compared to HC.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that both patients and siblings can indeed employ the reappraisal strategy in a laboratory setting, which is likely to be more structured and less complex than situations encountered in daily life. Barbalat et al [54] demonstrated that an increase of complex contextual information was related to reduced task performance in patients with schizophrenia. Interestingly, an increase of complex contextual information was associated with hypoactivation in the left VLPFC in patients compared to HC.…”
Section: Discussionmentioning
confidence: 99%
“…This result showing PFC dysfunction in medication-free patients with schizophrenia extends numerous previous neuroimaging studies on working memory and executive functions in this patient group (2, 58, 1214, 19). The failure to activate the frontopolar cortex in patients may reflect an impairment in retrieving information from working memory or inappropriate use of strategies involving switching processes since this brain region is frequently implicated in working memory (25), memory retrieval (26) and when combining working memory with task switching processes (27, 28). As noted previously, while the majority of neuroimaging studies of working memory in schizophrenia, particularly those using PET, have reported reduced DLPFC activity compared to healthy young controls (2,5,6,29), there are also a number of reports of hyperfrontality (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…Forde, Rusted, Mennie, Land, and Humphreys (2010) showed that a patient with disorganisation syndrome (resulting from a bilateral damage of the superior and middle frontal and temporal gyri) looked at more task-irrelevant objects than controls did during the task of making a cup of tea. Alterations in executive function (Nieoullon, 2002;Rajji, Ismail, & Mulsant, 2009;Rajji & Mulsant, 2008;Zayat, Rempfer, Gajewski, & Brown, 2011) and dorsolateral prefrontal cortex function are considered to be central in schizophrenia (Arnone et al, 2009;Barbalat, Chambon, Franck, Koechlin, & Farrer, 2009;van den Heuvel, Mandl, Stam, Kahn, & Hulshoff Pol, 2010;Weinberger & Berman, 1996).…”
Section: Introductionmentioning
confidence: 99%